Catch per unit effort, condition factor and length-weight relationship of albacore tuna (Thunnus alalunga), yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus) in the longline tuna fishery in the eastern Pacific Ocean - Bruno Thierry, Nyatchouba Nsangue; Cheng, Zhou; Pandong Achille, Njomoue; Richard, Kindong; Xu, Liuxiong (Indian Journal of Fisheries, 2021)
Highly migratory tuna species play an important economic role and ecosystem function worldwide. They are mainly caught in tropical and subtropical areas of the Pacific, Atlantic and Indian oceans. Data collected by the Chinese longline fishery in the high seas of the Eastern Pacific Ocean from 2014 to 2015 were analysed to estimate the catch per unit effort (CPUE), length and weight frequency, length-weight relationship, relative condition factor and Fulton’s condition factor for albacore tuna (Thunnus alalunga), yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus). The results showed that this fishing technique was highly selective for these three species. Albacore tuna represented the major portion of the catches at 76.17%. Yellowfin and bigeye tuna represented 8.24 and 11.68% of the total of specimens, respectively. The remaining 3.9% were bycatch such as Katsuwonus pelamis, Acanthocybium solandri, Ruvettus pretiosus, Xiphias gladius, Lampris guttatus, Carcharodon carcharias and Scomberomorus guttatus. The average fork length for albacore tuna was 90-100 cm; yellowfin tuna, 100-130 cm and bigeye tuna, 125-165 cm. The average weight for albacore tuna was 15-20 kg; yellowfin tuna, 20-50 kg and bigeye tuna, 35-55 kg. The CPUE (based on fish per one thousand hooks) for albacore, yellowfin tuna and bigeye tuna ranged from 1.6 to 9.82, 1.07 to 2.66 and 1.06 to 3.45, respectively. The parameters of the length-weight relationship showed a negative allometric growth regression of 2.7135 for albacore tuna, 2.3275 for yellowfin tuna and 2.4047 for bigeye tuna. Nevertheless, the albacore and yellowfin tuna females were characterised by positive allometry (b>3). The analyses also showed that the relative condition factors (Krel) of the three fish species were greater than one, implying that they were in good physiological condition, good water quality and healthy organisms. Keywords: China, Fishing effort, Fish per hook, Tuna